Odpowiedź :
Odpowiedź:
a) 17 + ( - 18) = - ( 18 - 17) = - 1
b) - 52 + (-8) = - ( 52 + 8) = - 60
c) 23 + (-19) = 23 - 19 = 4
d) - 7 + (-16) = - ( 7 + 16) = - 23
e) - 66 - ( -28) = - 66 + 28 = - ( 66 - 28) = - 38
f) - 33 - 60 = - ( 33 + 60) = - 93
g) - 86 - 13 = - ( 83 + 13) = - 96
h) 25 - ( -32) = 25 + 32 = 57
Szczegółowe wyjaśnienie:
Odpowiedź:
a) 17 + (-18)= 17 - 18 = -1
b) -52 + (-8)= -52 - 8= - 60
c) 23 + ( -19)= 23 - 19= 4
d) -7 + (-16)= - 7 - 16= - 23
e) -66 - (- 28)= -66 + 28= - 38
f) -33-60 = -93
g) -86 -13 = - 99
h) 25 - (-32) = 25 + 32= 57
Szczegółowe wyjaśnienie:
Jeśli mamy przed nawiasem znak minus i w nawiasie znak minus to daje nam plus